Autistic Aura! (Advancements in Homeopathic Research, 2022)
Background: Autism is a neuro-developmental  disorder that is characterized by impairment of the  ability of communication and social interaction.  It is commonly referred to as Autism Spectrum  Disorder. The article tries to share the experience  of the author dealing with autistic patients in the  clinical practice, their unpleasant aura along with  the importance of mother’s history during pregnancy  that has an effect on the child, and the homoeopathic  approach including the supportive treatment as well.  All the above mentioned aspects collectively help a  homoeopath to confidently manage such cases.
Keywords: Autism Spectrum Disorder; Genetic mutation; Homoeopathy; Hyperactivity; Ketogenic diet; Neuro-developmental disorder